Odpowiedź :
x:2-(x-3):4=2+x:5+(x-5):2 /*20
20*x:2-20*(x-3):4=20*2+20*x:5+20*(x-5):2
10x-5(x-3)=40+4x+10(x-5)
10x-5x+15=40+4x+10x-50
5x-14x=-10-15
-9x=-25
x=25/9
20*x:2-20*(x-3):4=20*2+20*x:5+20*(x-5):2
10x-5(x-3)=40+4x+10(x-5)
10x-5x+15=40+4x+10x-50
5x-14x=-10-15
-9x=-25
x=25/9
x/2 - x-3/4=2+x/5+ x-5/2 /*20
10x-5(x-3)=40+4x+10(x-5)
10x-5x+15=40+4x+10-50
10x-5x-4x-10x=40-50-15
-9x=-25/:(-9)
x=25/9= 2 7/9
10x-5(x-3)=40+4x+10(x-5)
10x-5x+15=40+4x+10-50
10x-5x-4x-10x=40-50-15
-9x=-25/:(-9)
x=25/9= 2 7/9